The Emergence of the Dutch Housewife Revised. How Shifts in Local Labour Market Structures Shaped Dutch Unmarried Women’s Labour Force Participation, 1812–1929 - Corinne Boter (Historical Life Course Studies)
Most studies on the long-term development of female labour force participation argue that social norms and rising wages were key drivers. However, the majority of these conclusions apply to married women. Instead, this study zooms in on unmarried women. Based on nearly 2 million marriage records that have been digitised by Kees Mandemakers' LINKS project, it shows that there were large regional differences in the levels of labour force participation that were closely connected to local job opportunities. This research concludes that even though social norms and income levels were indeed important, local sectoral employment shares were the key driver of Dutch unmarried women's work during the long-19th century.